Parent Education and Future Transition to Cigarette Smoking: Latinos' Diminished Returns - Assari, Shervin; Boyce, Shanika; Caldwell, Cleopatra H.; Bazargan, Mohsen (Frontiers in Pediatrics, 2020)
Background: High parent education is protective against youth health risk behaviors such as tobacco use. According to the Minorities' Diminished Returns theory, however, higher parent education seems to exert less protection for the ethnic minority relative to the majority groups. Objectives: To explore ethnic differences in the effects of parent education on the transition to cigarette smoking in a national sample of American never-smoker adolescents. Methods: This longitudinal study used data of waves 1 and 4 of the Population Assessment of Tobacco and Health (PATH 2013–2018). This analysis included 5,021 American youth who were never smokers at baseline (2013) and were followed for 4 years. Transition to cigarette smoking was the dependent variable. Parent education was the independent variable. Youth age, youth gender, and family structure were the covariates. Ethnicity was the moderating variable. Results: From the 5,021 American youth who were never smokers at baseline (2013), 89.4% continued as never smokers, and 10.6% became ever-smokers. Overall, 4.0% were current smokers at wave 4. Overall, a higher parent education was associated with lower odds of transitioning to ever and current cigarette smoker at the end of the 4th year. Parent education, however, showed significant interaction with Latino ethnicity on both outcomes suggesting smaller protective effects of high parent education against transitioning to tobacco use for Latino than for non-Latino youth. Conclusions: In the U.S., ethnicity alters the magnitude of the protective effect of parent education against youth transition to tobacco use. While high parent education is protective against transitioning to become a cigarette smoking overall, non-Latinos (a socially privileged group) gain more and Latino youth (a socially marginalized group) gain least from such a resource. In addition to addressing the SES gap, policymakers should identify and address mechanisms by which ethnic minority youth remain at risk of tobacco use, even when they are from highly educated families.